The emergence of social media for natural disasters management: A big data perspective - Athanasis, Nikos; Themistocleous, Marinos; Kalabokidis, Kostas; Papakonstantinou, Apostolos; Soulakellis, Nikos; Palaiologou, Palaiologos (My University, 2018)
Social media is rapidly emerging as a potential resource of information capable to support natural disasters management. Despite the growing research interest focused on using social media during natural disasters, many challenges may arise on how to handle the 'big data' problem: huge amounts of geo-social data are available, in different formats and varying quality that must be processed quickly. This article presents a state-of-the-art approach towards the enhancement of decision support tools for natural disaster management with information from the Twitter social network. The novelty of the approach lies in the integration of Geographic Information Systems (GIS) modeling outputs with real-time information from Twitter. A first prototype has been implemented that integrates geo-referenced Twitter messages into a Web GIS for wildfire risk management and real-time earthquake monitoring. Following a highly scalable architecture that relies on big data components, the proposed methodology can be applied in different geographical areas, different types of social media and a variety of natural disasters. The article aims at highlighting the role of social big data, towards a more sophisticated transfer of knowledge among civil protection agencies, emergency response crews and affected population.
Keywords: Social media; Big Data; Twitter; Real-time disaster managemen; Civil protection; GIS